Process Optimization of Hydrogen Production via the Water–Gas Shift Reaction Using CO Recycle and Exothermic Reactor Operation - Dias Fitriana; Nova Christiana; Olivia Refa Kusumawati; Salsadila Nur Fatima Azzahra (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Hydrogen production via the Water–Gas Shift Reaction (WGSR) is limited by thermodynamic equilibrium, restricting carbon monoxide (CO) conversion and process efficiency. The baseline process achieved 80.07% CO conversion, while the modified design incorporated CO recycle and controlled exothermic operation at 200° C. These changes significantly improved CO conversion to approximately 98%, reducing raw material losses and enhancing hydrogen yield. The results demonstrate that integrating recycle streams and thermal management strategies effectively overcomes equilibrium constraints for sustainable hydrogen production. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCRE Publishing Group. This is an openaccess article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).